Reflection on Religion and Citizenship in a Post-Secular Society - Leddy, Mary Joanna (Toronto journal of theology, 2015)
The street as a meeting point or shared space where strangers become neighbours: some reflections on a fundamental religious shift towards perception with respect to a house for refugees. In its tenor is an implicit argument that the shift shared by all religions involves refocusing our orientation from that of individual or group possessiveness and masters of the universe to awareness that we are inhabitants of a world that we have not created. Acceptance of responsibility and gratitude that the world is a gift and not a possession are the appropriate attitudes for the common good that can be shared with newcomers, and what has been articulated by the Czech president and playwright Vaclav Havel.